Empowering young people—the impact of camp experiences on personal resources, well-being, and community building - Kirchhoff, Esther; Keller, Roger; Blanc, Barbara (Frontiers in Psychology, 2024)
Personal resources and resources of the sociocultural environment help children and adolescents to successfully cope with challenges in everyday life, which is associated with better individual well-being. SCOUT, the 'Study on Competence development in OUT-of-school settings', investigated whether participation in a summer camp enhanced adolescents' personal resources, wellbeing, and readiness to contribute to the community. The research took place during the Swiss National Jamboree of the Swiss Guide and Scout Movement, a two-week event in the summer of 2022, with a paper-pencil pretest (beginning of the camp -T1) and posttest (end of the camp -T2) survey (N = 607, aged 14-17). Confirmatory factor analyses were used to examine whether personal resources, well-being, and readiness to contribute to the community changed over time, and structural equation models were applied to test the direct and indirect effects of caring support from group leaders on the development of these variables. In less than two weeks, camp participants demonstrated increased empathy, emotional selfcontrol, optimism, and assertiveness. Furthermore, the adolescents reported more positive emotions, higher self-esteem, and stronger readiness to contribute to the community. Group leaders played a crucial role by influencing the positive development of well-being and readiness to contribute to the community both directly and indirectly through the promotion of personal resources. The findings indicate that young people benefit not only from participating in collaborative activities in a stimulating environment, but also from caring support provided by their group leaders.